Aerogel composite material and method for manufacturing aerogel composite material

By immersing the aerogel powder in the porous fiber material by applying an alternating electric field, the problems of high equipment costs, large energy consumption and poor dispersion in the prior art are solved, and the low cost, low energy consumption preparation and good uniformity of the aerogel composite material are achieved.

CN119569476APending Publication Date: 2025-03-07OWENS CORNING (HANGZHOU) FIBERGLASS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311152915.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, when preparing aerogel composite materials, the equipment cost is high and the energy consumption is high. The dispersion of aerogel powder in the fiber material is poor, and good uniformity of the supercritical drying method cannot be achieved.

Method used

By applying an alternating electric field, the aerogel powder is immersed in the porous fiber material, and the oscillation of the alternating electric field is used to uniformly distribute the aerogel powder in the fiber material, avoiding the use of solvents and drying process.

Benefits of technology

The low-cost and low-energy-consuming preparation of aerogel composite materials is achieved, and the distribution uniformity and performance of aerogel powder are maintained well, and good thermal insulation performance is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569476A_ABST
    Figure CN119569476A_ABST
Patent Text Reader

Abstract

The invention discloses an aerogel composite material and a preparation method thereof. The aerogel composite material comprises a porous fiber material and aerogel powder distributed in the porous fiber material. The aerogel powder is impregnated within the porous fibrous material by applying an alternating electric field to the porous fibrous material. The aerogel powder is impregnated in the porous fiber material through the alternating electric field, and the impregnation amount of the aerogel powder is large and uniform, so that the aerogel composite material has better thermal insulation performance, the process is simple, and the production cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aerogels, and in particular to an aerogel composite material and a method for manufacturing the aerogel composite material. Background Art

[0002] Aerogel composites are a new type of advanced material, made by combining nano-aerogel particles and fiber materials through a special process. They are lightweight, highly effective in thermal insulation, fireproof, and environmentally friendly, and are widely used in construction, petroleum, aerospace, and other fields.

[0003] Currently, aerogel composite materials are mainly manufactured by supercritical drying. The supercritical drying method is to utilize the special properties of supercritical fluid (such as carbon dioxide) to replace the solvent in the sol-gel pre-impregnated in the fiber material, thereby realizing the transformation of sol-gel into aerogel, and at the same time making the aerogel grow in situ in the fiber material to produce an aerogel composite material (such as Chinese patents CN100540257C and CN105906298A). The supercritical drying method requires supercritical conditions, the cost of supercritical drying equipment is large, the process operation is complex, the process energy consumption is extremely high, and there are certain restrictions on the choice of precursors.

[0004] In addition to supercritical drying, several technologies have been developed to produce aerogels using atmospheric pressure drying. This method involves pre-modifying the sol-gel to make it hydrophobic, converting it into aerogel at ambient pressure and temperature, or at ambient pressure and high temperature (e.g., Chinese patents CN103771428A and CN109806817A). While the atmospheric pressure drying method offers low equipment cost and energy consumption, its further industrialization is limited by its limited ability to produce aerogel powders on a large scale, preventing the in-situ preparation of aerogel composites.

[0005] In recent years, numerous studies have focused on preparing aerogel composites by incorporating aerogel powder prepared by atmospheric drying into fiber mats through specialized processes. The most common approach involves preparing aerogel powder into an aerogel slurry, incorporating it into fiber materials via impregnation, and then evaporating the solvent (e.g., Chinese patents CN112301732B and CN114835435A). However, the slurry preparation process can damage the aerogel's nanoporous structure, resulting in performance degradation. Furthermore, the entire process requires large amounts of solvent and drying equipment, resulting in high costs and energy consumption. Other approaches, designed to avoid the use of solvents, involve spreading aerogel powder onto fiber mats manually or by electrostatic spraying, followed by a needle punching process (CN 115874348B). However, the dispersion of aerogel powder in fiber materials remains poor, failing to achieve the high uniformity of aerogel composites prepared by supercritical drying.

[0006] The use of aerogel powders for secondary compounding to prepare aerogel composites can greatly reduce the production cost of aerogel materials and expand their application in industrial production. However, the limitations of compounding technology have hindered its development.

[0007] Providing a secondary composite technology with low process investment cost, low production energy consumption, simple preparation process, excellent aerogel powder distribution effect and good pore structure and performance is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0008] The Summary of the Invention introduces a series of simplified concepts that will be further described in the Detailed Description of the Invention. The Summary of the Invention is not intended to limit the key features and essential features of the claimed technical solution, nor is it intended to determine the scope of protection of the claimed technical solution.

[0009] The present invention provides an aerogel composite material, comprising:

[0010] porous fibrous materials;

[0011] Aerogel powder distributed in the porous fiber material, wherein the aerogel powder is impregnated in the porous fiber material by applying an alternating electric field to the porous fiber material, wherein the density of the aerogel powder is in the range of 0.01 g / cm 3 Up to 0.5g / cm 3 , the average particle size of the aerogel powder is less than or equal to 500um.

[0012] In a specific embodiment, the voltage range of the alternating electric field is 0.1 KV to 50 KV, and the frequency range is 1 Hz to 800 Hz; the application time of the alternating electric field is 30 seconds to 5 minutes.

[0013] In a specific embodiment, the density of the aerogel powder ranges from 0.03 g / cm 3 to 0.1 g / cm 3 , and the average particle size of the aerogel powder is less than or equal to 50 μm.

[0014] In a specific embodiment, the porous fiber material is selected from glass fiber mat, glass fiber non-woven fabric, glass fiber woven fabric, ceramic fiber mat, paper, polyurethane fiber mat, carbon fiber mat, polypropylene fiber mat, polypropylene and glass fiber composite mat and combinations thereof.

[0015] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 20g / m 2 Up to 500g / m 2 The thickness is between 0.3mm and 4mm, and the air permeability is 200L / m 2 / s to 3000L / m 2 / s.

[0016] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 50g / m 2 Up to 150g / m 2 The thickness is between 0.5mm and 1.5mm, and the air permeability is 500L / m 2 / s to 2000L / m 2 / s.

[0017] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 90g / m 2 Up to 135g / m 2 The thickness is between 0.8mm and 1.3mm, and the air permeability is 1100L / m 2 / s to 1800L / m 2 / s.

[0018] In a specific embodiment, the polypropylene and glass fiber composite felt is made by blending polypropylene fiber and glass fiber, and the density of the polypropylene and glass fiber composite felt is 20kg / m 3 Up to 200kg / m 3 The thickness is between 1mm and 20mm.

[0019] In a specific embodiment, the density of the polypropylene and glass fiber composite felt is 50 kg / m 3 Up to 150kg / m 3 The thickness is between 3mm and 10mm.

[0020] In one embodiment, the aerogel powder is added with an additive for suppressing thermal radiation, wherein the additive is selected from at least one of silicon carbide, boron carbide, titanium oxide, and boron nitride. The weight ratio of the additive to the aerogel powder is in a range of 1 wt% to 15 wt%.

[0021] In a specific embodiment, the weight ratio of the additive to the aerogel powder ranges from 5 wt % to 12 wt %.

[0022] In a specific embodiment, the weight ratio of the aerogel powder to the aerogel composite material ranges from 1 wt % to 50 wt %.

[0023] The present invention also provides a method for manufacturing the aerogel composite material as described above, characterized in that the method comprises the following steps:

[0024] The aerogel powder is impregnated into the porous fiber material by applying an alternating electric field, wherein the voltage of the alternating electric field is in the range of 0.1 KV to 200 KV, the frequency is in the range of 0.1 Hz to 800 Hz, and the density of the aerogel powder is in the range of 0.01 g / cm 3 Up to 0.5g / cm 3 , the average particle size of the aerogel powder is less than or equal to 500um.

[0025] In a specific embodiment, the alternating electric field is applied for a time period of 30 seconds to 5 minutes.

[0026] In a specific embodiment, the method further comprises the steps of applying aerogel powder to the surface of the porous fiber material, and / or applying aerogel powder to a loader, wherein the loader is at least partially subjected to the alternating electric field;

[0027] In a specific embodiment, the porous fiber material and the aerogel powder are placed between a lower electrode and an upper electrode, the electrodes being electrically insulated from each other by a dielectric and connected to a power supply so as to subject the porous fiber material and the aerogel powder to the alternating electric field.

[0028] In a specific embodiment, the density of the aerogel powder is in the range of 0.03 g / cm 3 to 0.1g / cm 3 , the average particle size of the aerogel powder is less than or equal to 50 μm.

[0029] In a specific embodiment, the porous fiber material is selected from glass fiber mat, glass fiber non-woven fabric, glass fiber woven fabric, ceramic fiber mat, paper, polyurethane fiber mat, carbon fiber mat, polypropylene fiber mat, polypropylene and glass fiber composite mat and combinations thereof.

[0030] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 20g / m 2 Up to 500g / m 2 The thickness is between 0.3mm and 4mm, and the air permeability is 200L / m 2 / s to 3000L / m 2 / s.

[0031] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 50g / m 2 Up to 150g / m 2 The thickness is between 0.5mm and 1.5mm, and the air permeability is 500L / m 2 / s to 2000L / m 2 / s.

[0032] In a specific embodiment, the surface density of the glass fiber nonwoven fabric is 90g / m 2 Up to 135g / m 2 The thickness is between 0.8mm and 1.3mm, and the air permeability is 1100L / m 2 / s to 1800L / m 2 / s.

[0033] In a specific embodiment, the polypropylene and glass fiber composite felt is made by blending polypropylene fiber and glass fiber, and the density of the polypropylene and glass fiber composite felt is 20kg / m 3 Up to 200kg / m 3 The thickness is between 1mm and 20mm.

[0034] In a specific embodiment, the density of the polypropylene and glass fiber composite felt is 50 kg / m 3 Up to 150kg / m 3 The thickness is between 3mm and 10mm.

[0035] In a specific embodiment, an additive for suppressing thermal radiation is added to the aerogel powder, and the additive includes at least one of silicon carbide, boron carbide, titanium oxide, and boron nitride. The weight ratio of the additive to the aerogel powder ranges from 1 wt% to 15 wt%.

[0036] In a specific embodiment, the weight ratio of the additive to the aerogel powder ranges from 5 wt % to 12 wt %.

[0037] The present invention provides an aerogel composite material. One of the innovative points of the aerogel composite material provided by the present invention is that an alternating electric field is applied to the process of preparing the aerogel composite material, thereby making the aerogel composite material of the present invention have more outstanding technical advantages compared to the aerogel composite material manufactured by the supercritical drying method or the slurry impregnation method or other existing technologies in the prior art. For example, compared with the supercritical drying method, there is no need to use complex supercritical equipment, and no high energy consumption is required to generate supercritical fluid. Only aerogel powder prepared by the alternating electric field with a simple structure and the atmospheric drying method is needed, and the manufacturing process is simple. It can manufacture aerogel composite materials while meeting the requirements of uniform distribution of aerogel powder, with low investment cost and low energy consumption. Compared with the aerogel slurry impregnation method, because no solvent impregnation is required, the destruction of the aerogel powder structure is avoided, so that the aerogel composite material has better performance. At the same time, the process does not include the use of solvents and drying, which reduces a lot of energy consumption.

[0038] In addition, the aerogel powder is impregnated into the porous fiber material through an alternating electric field. The aerogel powder impregnation amount is large and uniform, so that the aerogel composite material has good thermal insulation performance, and the process is simple and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The following drawings of the present invention are incorporated herein as part of the present invention for understanding the present invention. The drawings show embodiments of the present invention and the description thereof is used to explain the principle of the present invention.

[0040] In the attached figure:

[0041] Figure 1 This is a scanning electron microscope photograph of a vertical cross-section of the aerogel composite material in Example 1 of the present invention;

[0042] Figure 2a This is a scanning electron microscope photograph of a vertical cross-section of the aerogel composite material in Example 2 of the present invention;

[0043] Figure 2b This is a scanning electron microscope photograph of the front side of the aerogel composite material in Example 2 of the present invention;

[0044] Figure 2c This is a scanning electron microscope photograph of the back side of the aerogel composite material in Example 2 of the present invention;

[0045] Figure 3a This is a scanning electron microscope photograph of a vertical cross-section of the aerogel composite material in Comparative Example 1 according to the present invention;

[0046] Figure 3b This is a scanning electron microscope photograph of the front side of the aerogel composite material in Comparative Example 1 according to the present invention;

[0047] Figure 3c This is a scanning electron microscope photograph of the back side of the aerogel composite material in Comparative Example 1 according to the present invention;

[0048] Figure 4a This is a scanning electron microscope photograph of a vertical cross-section of the aerogel composite material in Comparative Example 2 of the present invention;

[0049] Figure 4b This is a scanning electron microscope photograph of the front side of the aerogel composite material in Comparative Example 2 according to the present invention;

[0050] Figure 4c This is a scanning electron microscope photograph of the back side of the aerogel composite material in Comparative Example 2 according to the present invention. DETAILED DESCRIPTION

[0051] In the following description, numerous specific details are provided to provide a more thorough understanding of the present invention. However, it will be apparent to those skilled in the art that the present invention may be practiced without one or more of these details. In other instances, certain technical features well known in the art are not described in detail to avoid confusion with the present invention.

[0052] To provide a thorough understanding of the present invention, the following description provides a detailed description of the aerogel composite material and methods for making the aerogel composite. Obviously, the present invention is not limited to the specific details familiar to those skilled in the art of aerogels. Preferred embodiments of the present invention are described below in detail, however, the present invention may also have other embodiments beyond these detailed descriptions.

[0053] It should be noted that the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of the features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or combinations thereof.

[0054] Exemplary embodiments of the present invention will now be described in greater detail with reference to the accompanying drawings. However, these exemplary embodiments may be implemented in a variety of different forms and should not be construed as being limited to the embodiments set forth herein. It should be understood that these embodiments are provided to make the disclosure of the present invention thorough and complete and to fully convey the concepts of these exemplary embodiments to those of ordinary skill in the art.

[0055] In order to at least partially solve the above problems, the first aspect of the present invention provides an aerogel composite material. One of the innovative points of the aerogel composite material provided by the present invention is that an alternating electric field is applied to the process of preparing the aerogel composite material, thereby making the aerogel composite material of the present invention have more outstanding technical advantages compared to the aerogel composite materials manufactured by supercritical drying method or slurry impregnation method or other existing technologies in the prior art. For example, compared with the supercritical drying method, there is no need to use complex supercritical equipment, and no high energy consumption is required to generate supercritical fluid. Only aerogel powder prepared by using a simple alternating electric field and atmospheric pressure drying method is needed, and the manufacturing process is simple. It can manufacture aerogel composite materials while meeting the requirements of uniform distribution of aerogel powder, with low investment cost and low energy consumption. Compared with the aerogel slurry impregnation method, because no solvent impregnation is required, the destruction of the aerogel powder structure is avoided, so that the aerogel composite material has better performance. At the same time, the process does not include the use of solvent and drying, which reduces a lot of energy consumption.

[0056] Specifically, the aerogel composite material disclosed in the present invention may include a porous fiber material and aerogel powder distributed in the porous fiber material. By applying an alternating electric field to the porous fiber material, the aerogel powder is impregnated into the porous fiber material, so that the aerogel powder can not only be impregnated into the porous fiber material, but also be impregnated relatively uniformly. Figure 1 as well as Figure 2a The following are scanning electron microscope photos of the aerogel composite materials of Examples 1 and 2 in vertical sections, compared with the comparative example. Figure 3a and Figure 4a , it can be seen that the aerogel powder in the aerogel composite material of the present invention is distributed more evenly and the impregnation amount is relatively large. In many embodiments, the weight ratio of aerogel powder to aerogel composite material can range from 1wt% to 50wt%.

[0057] An alternating electric field refers to an electric field whose magnitude and direction change over time. It is generated by an alternating current power supply, in which the charge oscillates between positive and negative, causing changes in the electric field. The alternating electric field has the characteristic of periodic variation, and its frequency describes the speed of change, measured in Hertz (Hz). The voltage range of the alternating electric field of the present invention can be 0.1 kV to 50 kV, the frequency range can be 1 Hz to 800 Hz, and the application time of the alternating electric field can be 30 seconds to 5 minutes. Those skilled in the art can adjust any of the above parameters according to actual use requirements and product conditions during the production process.

[0058] The density of the aerogel powder of the aerogel composite material of the present invention can be in the range of 0.01 g / cm 3 Up to 0.5g / cm 3The average particle size of the aerogel powder is less than or equal to 500 μm. Preferably, the density of the aerogel powder can be in the range of 0.03 g / cm 3 to 0.1g / cm 3 The average particle size of the aerogel powder is less than or equal to 50 μm. For example, the aerogel powder can be obtained from JIOS aerogel. Aerogel powder (Chinese patent CN103771428B and US patent US20220306833, which are incorporated into this specification in their entirety by reference).

[0059] The porous fiber material can be selected from glass fiber mat, glass fiber non-woven fabric, glass fiber woven fabric, ceramic fiber mat, paper, polyurethane fiber mat, carbon fiber mat, polypropylene fiber mat, polypropylene and glass fiber composite mat and combinations thereof. As a preferred porous fiber material, glass fiber non-woven fabric can be selected, and its surface density can be 20g / m 2 Up to 500g / m 2 The thickness can be between 0.3mm and 4mm, and the air permeability can be 200L / m 2 / s to 3000L / m 2 / s. Further preferably, the surface density can be 50g / m 2 Up to 150g / m 2 The thickness can be between 0.5mm and 1.5mm, and the air permeability can be 500L / m 2 / s to 2000L / m 2 / s, or the surface density is 90g / m 2 Up to 135g / m 2 The thickness is between 0.8mm and 1.3mm, and the air permeability is 1100L / m 2 / s to 1800L / m 2 / s.

[0060] As another preferred embodiment, the porous fiber material can also be selected to have a density of 50 kg / m 3 Up to 150kg / m 3 The present invention is not limited to the types of porous fiber materials specifically listed. Any porous fiber material known to those skilled in the art or a material equivalent to a porous fiber material that can accommodate aerogel powder falls within the scope of protection defined by the present invention.

[0061] To improve the thermal insulation and heat preservation properties of the aerogel composite material, an additive for suppressing thermal radiation may be added to the aerogel powder. For example, the additive may be selected from at least one of silicon carbide, boron carbide, titanium oxide, and boron nitride. The weight ratio of the additive to the aerogel powder may range from 1 wt% to 15 wt%. Preferably, the weight ratio of the additive to the aerogel powder ranges from 5 wt% to 12 wt%.

[0062] A second aspect of the present invention also provides a method for producing an aerogel composite material, which method may basically comprise the following steps:

[0063] Loading: applying aerogel powder to the surface of the porous fiber material, and / or applying aerogel powder to a loader, which is at least partially subjected to an alternating electric field; for example, the loader can be a conveyor belt or a rotary loader, etc., the conveyor belt can be located above the porous fiber material and at least partially located in the alternating electric field, the aerogel powder can be transported by the conveyor belt, and when the alternating electric field is applied, the aerogel powder located on the conveyor belt can be impregnated into the porous fiber material.

[0064] Processing: Aerogel powder is impregnated into a porous fiber material by applying an alternating electric field, wherein the voltage range of the alternating electric field can be 0.1kV to 200kV and the frequency range is 0.1Hz to 800Hz; the density of the aerogel powder is in the range of 0.01g / cm 3 Up to 0.5g / cm 3 The average particle size of the aerogel powder is less than or equal to 500 μm. The alternating electric field is applied for a time of 30 seconds to 5 minutes.

[0065] In an alternative embodiment, the porous fiber material and aerogel powder are placed between a lower electrode and an upper electrode, the electrodes being electrically insulated from each other by a dielectric and connected to a power supply so as to subject the porous fiber material and aerogel powder to an alternating electric field.

[0066] Furthermore, in order to better illustrate the aerogel composite material and the method for manufacturing the aerogel composite material provided by the present invention, the present invention provides a plurality of embodiments and comparative examples for illustrating that the present invention has more outstanding technical advantages compared with the prior art.

[0067] Example 1:

[0068] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%;

[0069] Owens Corning glass fiber nonwoven fabric, weight 125g / m2 , thickness 1.25mm, air permeability 1300~1350L / m 2 / s;

[0070] High-voltage alternating electric field: It consists of two electrodes, one of which is grounded and the other is supplied with high-voltage alternating current, with a maximum voltage of ±15kV, a sinusoidal wave, and a frequency of 600HZ.

[0071] Implementation process: Spread the aerogel powder evenly on the glass fiber non-woven fabric, place it in a high-voltage alternating electric field, and turn on the power to allow the powder to fully vibrate for 2 minutes. The powder will be impregnated into the pores in the non-woven fabric.

[0072] Results: The final aerogel powder accounts for 42wt% of the total material. Figure 1 This is a scanning electron microscope photograph of the vertical cross-section of the aerogel composite material in Example 1. It can be seen that the aerogel powder is evenly impregnated in the pores of the non-woven fabric from the upper surface to the lower surface of the porous fiber material. Due to the large and uniform impregnation amount of aerogel powder, the aerogel composite material has good thermal insulation performance.

[0073] Example 2:

[0074] Material: JIOS aerogel Aerogel powder, particle size D50 < 50 μm, density 0.03-0.1 g / cm3, porosity > 90%; Owens Corning glass fiber non-woven fabric, weight 100 g / m2, thickness 1 mm, air permeability 1700-1750 L / m2 / s;

[0075] High-voltage alternating electric field: It consists of two electrodes, one of which is grounded and the other is supplied with high-voltage alternating current, with a maximum voltage of ±20kV, a sinusoidal wave, and a frequency of 600HZ.

[0076] Implementation process: Spread the aerogel powder evenly on the glass fiber non-woven fabric, place it in a high-voltage alternating electric field, and turn on the power to allow the powder to fully vibrate for 2 minutes. The powder will be impregnated into the pores in the non-woven fabric.

[0077] Results: The final aerogel powder accounts for 32wt% of the total material. Figure 2a 、 2b 2c and 2d are scanning electron microscope photos of the aerogel composite material in Example 2 at the vertical cross section, front side and back side, respectively.

[0078] Compared with the control Figure 3a and Figure 4a It can be seen that the aerogel powder in the aerogel composite material of Example 2 is distributed more evenly and the impregnation amount is relatively large. Figure 3b and Figure 4b It can be seen that the aerogel powder on the front of the aerogel composite material of Example 2 is distributed more evenly and the impregnation amount is relatively large. Figure 3c and Figure 4c The distribution of aerogel powder on the back side of the aerogel composite material in the comparative example is shown. It can be seen that there is basically no aerogel powder. The reasons include insufficient impregnation amount and uneven distribution of aerogel powder. However, the aerogel powder on the back side of the aerogel composite material of Example 2 is more evenly distributed and the impregnation amount is relatively large.

[0079] Example 3:

[0080] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; silicon carbide powder, particle size 0.5μm~0.7μm, density 0.8~0.9g / cm 3 etc.; Owens Corning glass fiber non-woven fabric, weight 100g / m 2 , thickness 1mm, air permeability 1700~1750L / m 2 / s;

[0081] High-voltage alternating electric field: It consists of two electrodes, one of which is grounded and the other is supplied with high-voltage alternating current, with a maximum voltage of ±20kV, a sinusoidal wave, and a frequency of 600HZ.

[0082] Implementation process: Aerogel powder and silicon carbide powder are evenly dispersed in a ratio of 9:1 and spread on a glass fiber non-woven fabric. The fabric is then placed in a high-voltage alternating electric field. Power is applied to allow the powder to fully vibrate for 2 minutes. The powder will then penetrate into the pores of the non-woven fabric.

[0083] Results: The final weight ratio of aerogel and silicon carbide powder to the entire material is 41wt%.

[0084] Example 4:

[0085] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; glass fiber and polypropylene fiber blended felt, density ~90kg / m 3 , thickness ~ 6mm, air permeability 380 ~ 420L / m 2 / s

[0086] High-voltage alternating electric field: It consists of two electrodes, one of which is grounded and the other is supplied with high-voltage alternating current, with a maximum voltage of ±14kV, a sinusoidal wave, and a frequency of 600HZ.

[0087] Implementation process: Spread the aerogel powder evenly on the glass fiber non-woven fabric, place it in a high-voltage alternating electric field, and turn on the power to allow the powder to fully vibrate for 2 minutes. The powder will be impregnated into the pores in the non-woven fabric.

[0088] Results: The final aerogel powder accounts for 35wt% of the total material.

[0089] Comparative Example 1:

[0090] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; Owens Corning glass fiber non-woven fabric, weight 125g / m 2 , thickness 1.25mm, air permeability 1300~1350L / m 2 / s;

[0091] Electrostatic spraying: electrostatic high voltage 20KV, electrostatic current 40μA, powder discharge pressure 210KPa, atomization pressure 70KPa, powder supply barrel fluidization pressure 35KPa;

[0092] Implementation process: Place the non-woven fabric on a horizontal table, connect the electrostatic spraying device to the powder barrel, power on, adjust the parameters, turn on the switch and evenly apply the aerogel powder on the non-woven fabric three times in total;

[0093] Results: The final aerogel powder accounts for 12wt% of the total material. Figure 3a 、 3b 3c and 3c are scanning electron microscope photos of the aerogel composite material in Comparative Example 1 at the vertical cross section, front side and back side, respectively.

[0094] Comparative Example 2:

[0095] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; glass fiber and polypropylene fiber blended felt, weight 540g / m 2 , thickness 6mm, air permeability 380~420L / m 2 / s.

[0096] Electrostatic spraying: electrostatic high voltage 20KV, electrostatic current 40μA, powder discharge pressure 210KPa, atomization pressure 70KPa, powder supply barrel fluidization pressure 35KPa.

[0097] Implementation process: Place the blended felt on a horizontal table, connect the electrostatic spraying device to the powder barrel, power on, adjust the parameters, turn on the switch and evenly apply the aerogel powder on the non-woven fabric three times in total;

[0098] Results: The final aerogel powder accounts for 8wt% of the total material. Figure 4a 、 4b And 4c are scanning electron microscope photographs of the aerogel composite material in Comparative Example 2 in a vertical cross-section, front and back.

[0099] Comparative Example 3:

[0100] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; Owens Corning needle punched felt, weight 900g / m 2 , density 60kg / m 2 , thickness ~ 15mm, air permeability 100 ~ 300L / m 2 / s; solvent: ethanol;

[0101] Implementation: Aerogel powder was stirred and dispersed in ethanol to prepare a 10 wt% dispersion with a viscosity of 18.1 cP. The dispersion was then added to the glass fiber mat, and vacuum suction was applied to ensure complete immersion. The glass fiber mat was then air-dried at room temperature for 24 hours and then dried in a 200°C oven for 12 hours.

[0102] Results: The final aerogel powder accounts for 22 wt% of the total material. The specific surface area data of the aerogel after dispersion impregnation and drying are shown in Table 1.

[0103] Comparative Example 4:

[0104] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; Owens Corning needle punched felt, weight 900g / m 2 , density 60kg / m 2 , thickness ~ 15mm, air permeability 100 ~ 300L / m 2 / s; solvent: n-hexane;

[0105] Implementation: Aerogel powder was stirred and dispersed in n-hexane to prepare a 10wt% dispersion with a viscosity of 6.24 cP. The dispersion was then added to the glass fiber mat and vacuumed to completely saturate the mat. The mat was then air-dried at room temperature for 24 hours and then dried in a 200°C oven for 12 hours.

[0106] Results: The final aerogel powder accounts for 21 wt% of the total material. The specific surface area data of the aerogel after dispersion impregnation and drying are shown in Table 1.

[0107] Comparative Example 5:

[0108] Material: JIOS aerogel Aerogel powder, particle size D50<50um, density 0.03-0.1g / cm 3 , porosity>90%; Owens Corning glass fiber non-woven fabric, weight ~60g / m 2 , thickness ~ 0.6mm, air permeability 3000 ~ 3100L / m 2 / s; Solvent: 75% water + 25% ethanol; Implementation: Aerogel powder was stirred and dispersed in the solvent to prepare a 10wt% dispersion with a viscosity of 12.1 cP. The dispersion was added to the glass fiber mat and vacuumed to completely saturate it. The glass fiber mat was then air-dried at room temperature for 24 hours and then dried in a 200°C oven for 12 hours.

[0109] Results: The final aerogel powder accounts for 20 wt% of the total material. The specific surface area data of the aerogel after dispersion impregnation and drying are shown in Table 1.

[0110] Table 1 shows the changes in the pore structure of the aerogel powders in Comparative Examples 3, 4, and 5 after solvent treatment. The specific surface area of ​​the aerogel powder decreased to varying degrees, and the porosity, or pore volume, decreased significantly. This indicates that the nanopores in the aerogel powder were damaged to varying degrees, with the internal space of the nanopores collapsing, resulting in a smaller pore volume and a lower specific surface area. The present invention directly impregnates the aerogel powder into the porous fiber material through an alternating electric field, thus avoiding the problem of solution treatment that can damage the aerogel powder structure, resulting in the aerogel composite material of the present invention having better performance.

[0111] Table 1

[0112]

[0113] The present invention has been described through the above-described embodiments. However, it should be understood that the above-described embodiments are for illustrative and illustrative purposes only and are not intended to limit the present invention to the described embodiments. Furthermore, it will be understood by those skilled in the art that the present invention is not limited to the above-described embodiments and that various variations and modifications may be made based on the teachings of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. An aerogel composite material, characterized in that: include: Porous fiber materials; Aerogel powder distributed in the porous fiber material, wherein the aerogel powder is impregnated into the porous fiber material by applying an alternating electric field to the porous fiber material, wherein the density of the aerogel powder is in the range of 0.01 g / cm 3 Up to 0.5g / cm 3 , the average particle size of the aerogel powder is less than or equal to 500um.

2. The aerogel composite material according to claim 1, characterized in that: The voltage range of the alternating electric field is 0.1KV to 50KV, and the frequency range is 1HZ to 800HZ; the application time of the alternating electric field is 30 seconds to 5 minutes.

3. The aerogel composite material according to claim 1, characterized in that: The density of the aerogel powder is in the range of 0.03 g / cm 3 To 0.1g / cm 3 , the average particle size of the aerogel powder is less than or equal to 50um.

4. The aerogel composite material according to claim 1, characterized in that: The porous fiber material is selected from glass fiber felt, glass fiber non-woven fabric, glass fiber woven fabric, ceramic fiber felt, paper, polyurethane fiber felt, carbon fiber felt, polypropylene fiber felt, polypropylene and glass fiber composite felt and combinations thereof.

5. The aerogel composite material according to claim 4, characterized in that: The surface density of the glass fiber nonwoven fabric is 20g / m 2 Up to 500g / m 2 The thickness is between 0.3mm and 4mm, and the air permeability is 200L / m 2 / s to 3000L / m 2 / s.

6. The aerogel composite material according to claim 5, characterized in that: The surface density of the glass fiber nonwoven fabric is 50 g / m 2 Up to 150g / m 2 The thickness is between 0.5mm and 1.5mm, and the air permeability is 500L / m 2 / s to 2000L / m 2 / s.

7. The aerogel composite material according to claim 6, characterized in that: The surface density of the glass fiber nonwoven fabric is 90g / m 2 Up to 135g / m 2 The thickness is between 0.8mm and 1.3mm, and the air permeability is 1100L / m 2 / s to 1800L / m 2 / s.

8. The aerogel composite material according to claim 4, characterized in that: The polypropylene and glass fiber composite felt is made by blending polypropylene fiber and glass fiber. The density of the polypropylene and glass fiber composite felt is 20kg / m 3 Up to 200kg / m 3 The thickness is between 1mm and 20mm.

9. The aerogel composite material according to claim 8, characterized in that: The density of the polypropylene and glass fiber composite felt is 50kg / m 3 Up to 150kg / m 3 The thickness is between 3mm and 10mm.

10. The aerogel composite material according to claim 1, characterized in that: The aerogel powder is added with an additive for suppressing heat radiation, the additive is selected from at least one of silicon carbide, boron carbide, titanium oxide, and boron nitride, and the weight ratio of the additive to the aerogel powder is in the range of 1wt% to 15wt%.

11. The aerogel composite material according to claim 10, characterized in that: The weight ratio of the additive to the aerogel powder ranges from 5 wt % to 12 wt %.

12. The aerogel composite material according to claim 1, characterized in that: The weight ratio of the aerogel powder to the aerogel composite material ranges from 1 wt % to 50 wt %.

13. A method for producing an aerogel composite material according to any one of claims 1 to 12, characterized in that The method comprises the following steps: The aerogel powder is impregnated into the porous fiber material by applying an alternating electric field, wherein the voltage of the alternating electric field is in the range of 0.1 KV to 200 KV, the frequency is in the range of 0.1 Hz to 800 Hz, and the density of the aerogel powder is in the range of 0.01 g / cm 3 Up to 0.5g / cm 3 , the average particle size of the aerogel powder is less than or equal to 500um.

14. The method according to claim 13, characterized in that The application time of the alternating electric field is 30 seconds to 5 minutes.

15. The method according to claim 13, characterized in that The method further comprises the steps of applying aerogel powder to the surface of the porous fiber material, and / or applying aerogel powder to a loader, wherein the loader is at least partially subjected to the alternating electric field.

16. The method according to claim 13, characterized in that The porous fiber material and the aerogel powder are placed between a lower electrode and an upper electrode, the electrodes being electrically insulated from each other by a dielectric and connected to a power source so as to subject the porous fiber material and the aerogel powder to the alternating electric field.

17. The method according to claim 13, characterized in that The density of the aerogel powder is in the range of 0.03 g / cm 3 To 0.1g / cm 3 , the average particle size of the aerogel powder is less than or equal to 50um.

18. The method according to claim 13, characterized in that The porous fiber material is selected from glass fiber felt, glass fiber non-woven fabric, glass fiber woven fabric, ceramic fiber felt, paper, polyurethane fiber felt, carbon fiber felt, polypropylene fiber felt, polypropylene and glass fiber composite felt and combinations thereof.

19. The method according to claim 18, characterized in that The surface density of the glass fiber nonwoven fabric is 20g / m 2 Up to 500g / m 2 The thickness is between 0.3mm and 4mm, and the air permeability is 200L / m 2 / s to 3000L / m 2 / s.

20. The method according to claim 19, characterized in that The surface density of the glass fiber nonwoven fabric is 50 g / m 2 Up to 150g / m 2 The thickness is between 0.5mm and 1.5mm, and the air permeability is 500L / m 2 / s to 2000L / m 2 / s.

21. The method according to claim 20, characterized in that: The surface density of the glass fiber nonwoven fabric is 90g / m 2 Up to 135g / m 2 The thickness is between 0.8mm and 1.3mm, and the air permeability is 1100L / m 2 / s to 1800L / m 2 / s.

22. The method according to claim 18, characterized in that The polypropylene and glass fiber composite felt is made by blending polypropylene fiber and glass fiber. The density of the polypropylene and glass fiber composite felt is 20kg / m 3 Up to 200kg / m 3 The thickness is between 1mm and 20mm.

23. The method according to claim 22, characterized in that The density of the polypropylene and glass fiber composite felt is 50kg / m 3 Up to 150kg / m 3 The thickness is between 3mm and 10mm.

24. The method according to claim 13, characterized in that The aerogel powder is added with an additive for suppressing heat radiation, wherein the additive includes at least one of silicon carbide, boron carbide, titanium oxide, and boron nitride, and the weight ratio of the additive to the aerogel powder is in a range of 1wt% to 15wt%.

25. The method according to claim 24, characterized in that The weight ratio of the additive to the aerogel powder ranges from 5 wt % to 12 wt %.

Citation Information

Patent Citations

  • Methods to produce gel sheets

    CN100540257C

  • Silica aerogel power manufacturing system and manufacturing method using the same

    CN103771428A

  • Silica gel aerogel powder manufacturing system and manufacturing method

    CN103771428B

  • Glass fiber mat-reinforced silica aerogel and preparation method thereof

    CN105906298A

  • Integrative gel modification and drying system and method

    CN109806817A